2021
DOI: 10.1016/j.xinn.2021.100098
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic magnetic topological insulators

Abstract: van der Waals material MnBi 2 Te 4 is an intrinsic antiferromagnetic topological insulator -Under moderate magnetic field, MnBi 2 Te 4 may become a magnetic Weyl semimetal -MnBi 2 Te 4 and its family of materials have brought great progress in studying novel topological quantum states -Quantum anomalous Hall effect above the liquid-nitrogen temperature can be expected in MnBi 2 Te 4 -related systems ll www.cell.com/the-innovation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 105 publications
(404 reference statements)
0
44
0
4
Order By: Relevance
“…Very recently, antiferromagnetic domains as well as the A-type antiferromagnetic order were imaged in MnBi 2 Te 4 and Mn(Bi,Sb) 2 Te 4 bulk crystals by magnetic force microscopy (Sass et al, 2020a,b). More focused reviews of the MnBi 2 Te 4 family of compounds can be found in Ning and Mao, 2020;Wang et al, 2021;and Zhao and Liu, 2021.…”
Section: Mnbi2te4: An Intrinsic Magnetic Ti a Materials Propertiesmentioning
confidence: 99%
“…Very recently, antiferromagnetic domains as well as the A-type antiferromagnetic order were imaged in MnBi 2 Te 4 and Mn(Bi,Sb) 2 Te 4 bulk crystals by magnetic force microscopy (Sass et al, 2020a,b). More focused reviews of the MnBi 2 Te 4 family of compounds can be found in Ning and Mao, 2020;Wang et al, 2021;and Zhao and Liu, 2021.…”
Section: Mnbi2te4: An Intrinsic Magnetic Ti a Materials Propertiesmentioning
confidence: 99%
“…The protected surface state of topological insulator fits into this role for its long enough mean free path and lifetime and also for excluding the insulating and spin-degenerate bulk influence [13][14][15]. Tunable exchange gap from controlling magnetic doping further allows for demonstrating both massless and massive Dirac physics [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The realization of magnetic TIs has become recently the focus of intense research [10][11][12] with various candidates appearing in the literature [13][14][15][16][17][18][19][20][21]. The most prominent, MnBi 2 Te 4 [13,14], is a layered tetradymite compound with an A-type antiferromagnetic (AFM) order, i.e., with magnetization uniform in-plane but alternating from plane to plane along the stacking direction.…”
Section: Introductionmentioning
confidence: 99%